Methods and membranes

By mixing the stabilized dispersion of recombinant catalyst nanoparticles with ionic conductive polymer to form an ink, an ionic conductive film containing dispersed recombinant catalyst nanoparticles is produced, which solves the problem of high hydrogen permeability under high pressure difference in the prior art, and achieves low-cost and efficient film production.

CN119866394APending Publication Date: 2025-04-22JOHNSON MATTHEY HYDROGEN TECH LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380058591.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-29
Filing Date
2023-09-28
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing ionic conductive film has a high hydrogen permeability level under high pressure differential, which leads to safety problems and is difficult to scale and cost control for production methods.

Method used

By mixing the stabilized dispersion of the recombinant catalyst nanoparticles with the ionically conductive polymer to form an ink, an ionic conductive film containing the dispersed recombinant catalyst nanoparticles is produced.

Benefits of technology

It realizes the reduction of hydrogen permeability level under high pressure differential, improves the stability and dispersion of the membrane, reduces production costs, and is suitable for water electrolytic cells and fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866394A_ABST
    Figure CN119866394A_ABST
Patent Text Reader

Abstract

A method for producing an ion conducting membrane comprising a membrane layer comprising a reconstitution catalyst. The film layer is made from an ink comprising a stabilized dispersion of reconstitution catalyst nanoparticles. Also provided are ion conducting membranes for electrochemical devices, such as fuel cells or water electrolysers, having a membrane layer comprising a reconstitution catalyst, the membrane layer comprising dispersed reconstitution catalyst nanoparticles, a nanoparticle stabilizer, and an ion conducting polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to ion-conducting membranes suitable for use in electrochemical devices such as water electrolyzers and fuel cells, catalyst-coated membranes incorporating such ion-conducting membranes, and methods for their production. Background Art

[0002] The electrolysis of water can be performed in both alkaline and acidic systems to produce high-purity hydrogen and oxygen. Those electrolyzers that employ solid proton-conducting polymer electrolyte membranes or proton exchange membranes (PEMs) are referred to as proton exchange membrane water electrolyzers (PEMWEs). Those electrolyzers that utilize solid anion-conducting polymer electrolyte membranes or anion exchange membranes (AEMs) are referred to as anion exchange membrane water electrolyzers (AEMWEs).

[0003] Ion-conducting membranes such as PEMs and AEMs are also used in fuel cells. In a proton exchange membrane fuel cell (PEMFC), the membrane is proton-conducting and transports protons generated at the anode across the membrane to the cathode where they combine with oxygen to form water.

[0004] Catalyst coated membranes (CCMs) can be used in electrochemical devices such as electrolyzers and fuel cells. Such CCMs include an ion-conducting membrane such as a PEM or AEM, with at least one of an anode catalyst layer and a cathode catalyst layer applied to a face of the membrane.

[0005] For water electrolyzer applications, hydrogen evolution reaction (HER) catalysts are used in such cathode catalyst layers, for example HER catalysts comprising platinum (such as platinum on a carbon support). Oxygen evolution reaction (OER) catalysts are used in electrolyzer anode catalyst layers. For PEMWE applications, suitable OER catalysts include iridium or iridium oxide (IrOx), or oxides containing both iridium and ruthenium. For AEMWE applications, non-platinum group metal OER catalysts, such as alloys and oxides of nickel, cobalt, iron and copper, may also be used.

[0006] For fuel cell applications, an oxygen reduction reaction (ORR) catalyst is used in the cathode catalyst layer, and a hydrogen oxidation reaction (HOR) catalyst is used in the anode catalyst layer. For PEMFC applications, suitable cathode catalyst materials and anode catalyst materials include platinum group metals (PGMs) or alloys of PGMs with one or more other metals, such as platinum or alloys of platinum with one or more other metals.

[0007] A separate membrane layer, typically formed of a non-ion-conducting polymer, can be positioned around the edge region of the CCM, for example on the exposed surface of the ion-conducting membrane where no electrocatalyst is present (but will often overlap the edge of the electrocatalyst layer as well), to provide a seal to prevent the escape of reactant and product gases, to strengthen and reinforce the edge of the CCM, and to provide a suitable surface for supporting subsequent components (such as a subgasket or elastomeric gasket). An adhesive layer may be present on one or both surfaces of the sealing membrane layer.

[0008] The CCM can be incorporated into a membrane electrode assembly (MEA), which is essentially composed of five layers. The middle layer is a polymer ion-conducting membrane. On either side of the ion-conducting membrane there is an electrocatalyst layer containing an electrocatalyst designed for a specific electrolysis reaction. Finally, adjacent to each electrocatalyst layer is a gas diffusion layer or a porous transport layer, depending on the final MEA application and stack configuration. Such layers allow reactants to reach the electrocatalyst layer and allow products to leave.

[0009] It is desirable to reduce the thickness of such ion-conducting membranes to minimize electronic and ionic resistance. However, it is also important to minimize any hydrogen permeation through the membrane to avoid mixing of hydrogen with oxygen and the associated safety issues.

[0010] For water electrolyzers, it is beneficial to maintain low levels of hydrogen permeation even at high pressure differentials across the membrane. The use of high pressure during electrolyzer operation is advantageous because it reduces the compression requirements for the hydrogen produced and reduces operating costs. This has led to the use of membranes with thicknesses exceeding 125 μm and often approaching 200 μm or more. Examples of membranes currently in use include Nafion TM N115 (thickness 125μm) or Nafion TM N117 (thickness 175 μm).

[0011] It is known to produce proton exchange membranes including recombinant catalysts, which catalyze the reaction between hydrogen and oxygen to form water and thus reduce the hydrogen permeation level. For example, in WO2020 / 148545 (Johnson Matthey Fuel Cells Ltd), it is described that a catalyst containing platinum on a graphene carrier can be introduced into a proton exchange membrane. In addition, CN114874475 (Foshan Cleanest Energy Technology Co., Ltd. (FOSHAN CLEANESTENERGY CO LTD)) describes the use of platinum particles loaded on hollow polydopamine microspheres in proton exchange membranes. In this case, the platinum particles are positioned in the membrane on the surface of the catalyst support.

[0012] It is also known to incorporate platinum nanoparticles into ion-conducting membranes. For example, US10,476,094 (LG Chem Ltd) describes a reinforced membrane comprising a porous polymer support. Platinum nanoparticles are provided on both surfaces and on the surface in the pores of the porous polymer support. To prepare the membrane, the porous support is immersed in a solution of a platinum precursor, which is subsequently reduced by adding a reducing agent. This approach has a number of manufacturing disadvantages. For example, the impregnation of the porous polymer support in the platinum precursor solution can result in swelling and / or deformation of the support during impregnation, and such impregnation and drying methods are difficult to replicate on a large manufacturing scale. In addition, the requirement to co-localize the enhancer component and the platinum nanoparticles limits the scope that can be used to optimize performance by changing the membrane configuration, and limits the ability to disperse the nanoparticles.

[0013] A similar method involving local deposition of Pt nanoparticles onto the pores of a PTFE membrane is described in the following: "Reinforced and self-humidifying composite membrane for fuel cell applications"; Liu et al., Journal of Membrane Science, 330 (2009) 357-362. It is also described in US 2015 / 0236354 (Solvicore GMBH & Co. KG) that a colloidal dispersion comprising nano-sized noble metal particles and an ionomer component can be formed by dissolving a suitable noble metal precursor with a liquid acidic ionomer component, followed by a reduction step. This colloidal dispersion contains no other ingredients.

[0014] Incorporating recombinant catalyst particles into ion-conducting membrane layers remains challenging. It is difficult to reproducibly produce consistent inks containing ion-conducting polymers and catalyst particles that retain their properties when stored. Typically, this means that such inks must be prepared shortly before manufacturing, thus reducing manufacturing flexibility.

[0015] The addition of a recombination catalyst also increases the cost of the ion conducting membrane, so it is desirable to maximize the reduction in hydrogen permeation for a given amount of recombination catalyst.

[0016] There remains a need to further develop efficient and scalable methods for producing ion-conducting membranes, and to enhance such membranes to enable efficient operation at high pressure differentials across the membrane. Summary of the invention

[0017] The present inventors have surprisingly discovered that stabilized dispersions of recombinant catalyst nanoparticles can be advantageously combined with ion-conducting polymers to form inks suitable for ion-conducting membrane fabrication, and that such inks exhibit nanoparticle size stability over extended periods of time. The present inventors have also discovered that ion-conducting membranes can be produced using such inks, which inks exhibit excellent dispersion of catalyst nanoparticles within the membrane layer.

[0018] Thus, in a first aspect of the present invention there is provided a method for producing an ion conducting membrane comprising a membrane layer comprising a recombination catalyst, the method comprising the steps of:

[0019] (i) providing a stabilized dispersion of recombinant catalyst nanoparticles;

[0020] (ii) mixing the stabilized dispersion with an ionically conductive polymer to form an ink;

[0021] (iii) producing the film layer from the ink.

[0022] In a second aspect of the present invention, there is provided an ink for making an ion-conducting membrane, the ink comprising recombinant catalyst nanoparticles, a nanoparticle stabilizer and an ion-conducting polymer.

[0023] It has also been found that an ion-conducting membrane comprising a nanoparticle stabilizer and recombinant catalyst nanoparticles dispersed in an ion-conducting polymer layer can be produced. Such membranes have been found to provide an enhanced reduction in hydrogen permeation levels during testing as described in the Examples. Therefore, in a third aspect of the invention, an ion-conducting membrane, such as a proton exchange membrane or an anion exchange membrane, is provided, comprising a membrane layer containing a recombinant catalyst, the membrane layer comprising dispersed recombinant catalyst nanoparticles, a nanoparticle stabilizer and an ion-conducting polymer.

[0024] Such membranes are particularly suitable for use in water electrolyzers.

[0025] The ion-conducting membrane of the third aspect may be or may be obtained by the method of the first aspect.

[0026] The ion-conducting membrane of the third aspect has particular use as a component of a catalyst coated membrane (CCM). Thus, in a fourth aspect of the invention there is provided a CCM for an electrochemical device such as a water electrolyser or a fuel cell, the CCM comprising a membrane according to the third aspect.

[0027] Suitably, the CCM is used in a water electrolyser, such as a PEM water electrolyser. In such cases, the CCM comprises a cathode catalyst layer for catalyzing the hydrogen evolution reaction and / or an anode catalyst layer for catalyzing the oxygen evolution reaction. Typically, the cathode catalyst layer comprises platinum and / or the anode catalyst layer comprises iridium.

[0028] The CCM may also be used in a fuel cell, such as a PEM fuel cell. In such a case, the CCM includes a cathode catalyst layer for catalyzing an oxygen reduction reaction and / or an anode catalyst layer for catalyzing an hydrogen oxidation reaction.

[0029] In a fifth aspect of the present invention, there is provided a water electrolyser or a fuel cell, the water electrolyser or the fuel cell comprising the membrane according to the third aspect or the catalyst coated membrane according to the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A schematic diagram showing an example arrangement of the electrolyte membrane of the present invention.

[0031] Figure 2 A schematic diagram showing an example arrangement of a catalyst coated membrane of the present invention.

[0032] Figure 3 Shown are the results of stability testing of inks containing PVP-stabilized platinum nanoparticles and ion-conducting polymers.

[0033] Figure 4 Scanning electron microscopy-energy dispersive X-ray (SEM_EDX) analysis results of a film including a platinum-containing film layer are shown.

[0034] Figure 5 Shown are the results of hydrogen permeation tests of catalyst coated membranes.

[0035] Figure 6 Further hydrogen permeation test results of the catalyst coated membranes are shown. DETAILED DESCRIPTION

[0036] The preferred and / or optional features of the present invention will now be described. Unless the context otherwise requires, any aspect of the present invention may be combined with any other aspect of the present invention. Unless the context otherwise requires, any preferred and / or optional features of any aspect may be combined with any other features of the present invention individually or in combination.

[0037] The present invention provides a method for producing an ion-conducting membrane having a membrane layer containing a recombinant catalyst, and an ion-conducting membrane comprising such a membrane layer. Preferably, the ion-conducting membrane is a proton exchange membrane (PEM), such as a PEM for a water electrolyzer. However, it will be appreciated by those skilled in the art that the methods and membrane layers containing a recombinant catalyst described herein can also be used for other types of electrolyte membranes, such as PEMs for fuel cells, and anion exchange membranes for water electrolyzers, fuel cells, or other applications.

[0038] The recombinant catalyst-containing layer comprises recombinant catalyst nanoparticles. As used herein, the term nanoparticles refers to particles having a size in the range of 1 nm to 100 nm, inclusive.

[0039] A recombination catalyst is a catalyst that catalyzes the reaction between hydrogen and oxygen to form water. Thus, the recombination catalyst used in the ion-conducting membrane of the present invention may be any catalyst that is capable of catalyzing the reaction between hydrogen and oxygen to form water, thereby reducing or preventing the permeation of hydrogen or oxygen or both through the membrane.

[0040] Suitably, the recombination catalyst is selected from the list comprising:

[0041] i) platinum group metals (ie, the group of elements comprising platinum, palladium, iridium, rhodium, ruthenium and osmium);

[0042] ii)gold;

[0043] iii) base metals such as iron, nickel, cobalt or chromium;

[0044] iv) alloys containing one or more of the above elements;

[0045] v) mixtures of any of the above.

[0046] Suitably, the recombination catalyst comprises platinum or palladium, or consists essentially of platinum or palladium (i.e., the nanoparticles are platinum nanoparticles or palladium nanoparticles). Alternatively, the recombination catalyst may be platinum alloyed with one or more of the above elements, such as a platinum-palladium alloy, a platinum-iridium alloy, a platinum-cobalt alloy, or a platinum-ruthenium alloy.

[0047] Preferably, the recombinant catalyst nanoparticles in the dispersion are unloaded. The term "unloaded" will be easily understood by the technician. For example, it should be understood that the recombinant catalyst particles are not combined or fixed to a solid catalyst support (such as a carbon support) by physical or chemical bonds (such as by ionic bonds or covalent bonds) or non-specific interactions (such as van der Waals forces). The use of unloaded nanoparticles provides increased film stability during electrochemical operation, avoids corrosion via the catalyst support or degradation pathways of other chemical or electrochemical reactions, and enables greater dispersion in the film layer.

[0048] The method comprises the step (i) providing a stabilized dispersion of recombinant catalyst nanoparticles. It will be appreciated by those skilled in the art that the stabilized nanoparticle dispersion comprises solid catalyst nanoparticles in a liquid phase, the liquid phase comprising at least one nanoparticle stabilizer that interacts with the nanoparticles to prevent nanoparticle agglomeration. Such agents additionally act as capping agents during synthesis.

[0049] The method as described herein involves a first step of forming a stabilized nanoparticle dispersion prior to the step of mixing the stabilized dispersion with the ion-conducting polymer in a subsequent ink forming step. Thus, it will be appreciated by those skilled in the art that the stabilizer or each stabilizer used to form the stabilized nanoparticle dispersion is different from the ion-conducting polymer used to form the ink in step (ii).

[0050] Suitable nanoparticle stabilizers are selected from those agents that interact with the surface of the catalyst nanoparticles, prevent the aggregation and agglomeration of the catalyst nanoparticles and enable the formation of nanoparticle dispersions. This stabilization of the nanoparticle surface is generally by the interaction between the polar functional groups of the nanoparticles and the stabilizer. Typically, the stabilizer comprises an amide, carboxylic acid, sulfonic acid, amine, alcohol or ether functional group. It may be preferred that the stabilizer comprises an amide or ether functional group. It may be further preferred that the stabilizer comprises a tertiary amide group. In some embodiments, the stabilizer does not have an acidic functional group. In some embodiments, the stabilizer does not have a sulfonic acid functional group. Preferably, the nanoparticle stabilizer is water-soluble, such as a water-soluble polymer. Preferably, the nanoparticle stabilizer has a water solubility of at least 1 mg / mL, preferably at least 10 mg / mL or more preferably at least 100 mg / mL at 25°C.

[0051] It may be preferred that the stabiliser has a higher hydrophobicity and / or a lower water absorption value than the ion-conducting polymer used in step (ii).

[0052] Suitably, the stabilized dispersion comprises a polymeric nanoparticle stabilizer. It may be preferred that the stabilized dispersion comprises a polymeric nanoparticle stabilizer having a higher hydrophobicity and / or a lower water absorption value than the ion-conducting polymer used in step (ii). It may also be preferred that the polymeric nanoparticle stabilizer has a lower weight average molecular weight than the ion-conducting polymer used in step (ii).

[0053] It may further be preferred that the polymeric stabilizer comprises an amide functionality, such as a tertiary amide functionality, for example a pyrrolidone functionality (such as polyvinylpyrrolidone (PVP) or a copolymer comprising vinylpyrrolidone as the first polymerized unit).

[0054] Suitably, the stabiliser is polyvinylpyrrolidone (PVP).The use of PVP in the presence of a perfluorosulfonic acid (PFSA) polymer has been found to provide superior dispersion stability and provide greater nanoparticle dispersion stability than nanoparticles with PFSA alone.

[0055] Suitably, the stabilizer is a PVP having a weight average molecular weight in the range of 5,000 to 50,000, inclusive. This range is believed to provide a suitable balance between dispersion stability and ease of polymer processability. It may further be preferred that the polymer stabilizer is a polyvinyl pyrrolidone having a weight average molecular weight in the range of 8,000 to 45,000, inclusive.

[0056] Typically, the stabilized dispersion is formed in an aqueous medium such as water.

[0057] Suitably, the recombinant catalyst nanoparticles are prepared at 0.5 g L -1 Up to 10 g L -1 In the range of and including 0.5 g L -1 and 10 g L -1 In the case where the recombinant catalyst nanoparticles are platinum particles, such particles are typically present in an amount of 0.5 g Pt L -1 Up to 10g Pt L -1 In the range of and including 0.5g Pt L -1 and 10g Pt L -1 The nanoparticle concentration can be adjusted using techniques known to those skilled in the art, such as evaporation or cross-flow filtration.

[0058] Suitably, the dispersion formed in step (i) has a zeta potential more positive than +25 mV or more negative than -25 mV. The zeta potential may be measured using electrophoretic light scattering, for example using a Zetasizer Ultra (Malvern Panalytical).

[0059] Those skilled in the art will know the method for producing suitable catalyst nanoparticle dispersions. For example, the dispersion can be produced by continuous flow hydrothermal synthesis. Suitably, this synthesis can be carried out in a hybrid reactor, such as the hybrid reactor described in WO2015075439A1 (University of Nottingham) incorporated herein by reference.

[0060] Catalyst nanoparticle dispersions can also be produced by mixing a suitable catalyst precursor with a stabilizer in a solvent such as water, and then forming nanoparticles in situ. For example, in the case of platinum nanoparticles, a platinum precursor such as chloroplatinic acid (HPtCl), platinum nitrate or Pt (acac) can be mixed with a stabilizer in a solvent such as water, and then, for example, sodium borohydride or formaldehyde is used to reduce the platinum precursor to produce a dispersion. This example of preparation is described in Du, YK, Journal of Applied Polymer Science, Vol. 99, 23-36 (2006), which is incorporated herein by reference.

[0061] The method comprises the step (ii) mixing the stabilized dispersion with an ion-conducting polymer to form an ink. Typically, this is achieved by forming a dispersion of the ion-conducting polymer and then mixing this dispersion with the stabilized dispersion of the recombinant catalyst nanoparticles.

[0062] Those skilled in the art will be aware of suitable ion conducting polymers for use in preparing ion conducting membranes. The ion conducting polymer may be a proton conducting polymer or an anion conducting polymer, such as a hydroxy anion conducting polymer. Examples of suitable proton conducting polymers include perfluorosulfonic acid ionomers (e.g., (Chemours Company), (Asahi Kasei), Aquivion TM (Solvay Speciality Polymers), (Asahi Glass Co.) or ionomers based on sulfonated hydrocarbons, such as P, E or K series products are those available from FuMA-Tech GmbH (JSR Corporation, Toyobo Corporation, etc.). Examples of suitable anionic conductive polymers include A901 and A201 manufactured by Tokuyama Corporation, Fumasep FAA from FuMA-Tech GmbH, and Aemion polymers from Ionomr.

[0063] In the case where the membrane is used for a PEM electrochemical device, the ion-conducting polymer is suitably a proton-conducting polymer, and in particular a partially fluorinated sulfonic acid polymer or a fully fluorinated sulfonic acid polymer. Examples of suitable proton-conducting polymers include perfluorosulfonic acid (PFSA) polymers. It is preferred that the ion-conducting polymer is a PFSA polymer and has an equivalent mass (EW) greater than 750EW, greater than 760EW, greater than 770EW or greater than 790EW. For example, it is preferred that the ion-conducting polymer is a PFSA polymer with an equivalent mass in the range of 750EW to 1200EW and including 750EW and 1200EW (such as in the range of 770EW to 1000EW and including 770EW and 1000EW, or in the range of 800EW to 900EW and including 800EW and 900EW).

[0064] The ion-conducting polymer is usually dispersed in a mixture of an organic solvent and water. For example, the solvent can be a mixture of an alcohol (e.g., ethanol or propanol) and water. The volume ratio of the organic solvent (such as ethanol) to water can be in the range of 95:5 to 60:40 and include 95:5 and 60:40, such as in the range of 90:10 to 70:30 and include 90:10 and 70:30. The solvent is formulated to achieve the desired dispersion, coating and drying characteristics.

[0065] The ink may also include a free radical reducing additive (e.g., a peroxide free radical reducing additive such as ceria). For example, the free radical reducing additive (such as ceria) may be provided in the dispersion at a weight percentage in the range of 0.15 wt % to 0.35 wt %, including 0.15 wt % and 0.35 wt %, such as in the range of 0.20 wt % to 0.30 wt %, including 0.20 wt % and 0.30 wt %, relative to the weight of the ion conductive polymer. Once the stabilized dispersion is mixed with the ion conductive polymer, the free radical reducing agent is typically added to the ink.

[0066] The resulting ink typically comprises or consists essentially of:

[0067] (i) Ion-conducting polymers, such as proton-conducting polymers, for example PFSA ionomers. The ion-conducting polymers are typically present in an amount ranging from 5 wt % to 25 wt % and including 5 wt % and 25 wt %, such as 10 wt %

[0068] A weight percentage in the range of and including 10 wt % to 20 wt % is provided in the ink;

[0069] (ii) recombinant catalyst nanoparticles, such as palladium or platinum nanoparticles. Typically, the catalyst nanoparticles are present in the ink in an amount in the range of 0.01 wt % to 0.40 wt % and inclusive, relative to the total weight of the ink components, such as in the range of 0.01 wt % Pt to 0.40 wt % Pt and inclusive.

[0070] Pt and platinum nanoparticles with 0.40 wt % Pt;

[0071] (iii) a nanoparticle stabilizer, such as a polymeric nanoparticle stabilizer, for example PVP. Typically, the nanoparticle stabilizer is present in the ink in an amount ranging from 0.05 wt % to 2 wt % and including 0.05 wt % and 2 wt %, such as ranging from 0.05 wt % to 0.50 wt % and including 0.05 wt % and 0.50 wt % relative to the total weight of the ink components;

[0072] (iv) Optionally, a free radical reducing additive, such as cerium dioxide (CeO2), the amount of which is generally in the following weight percentages relative to the total weight of the ink components: within the range of and including 0.15 wt% to 0.35 wt%.

[0073] Wherein components (i) to (iv) are dispersed in a solvent, such as a mixture of an alcohol (eg ethanol or 1-propanol) and water, for example a volume ratio of alcohol:water: 95:5 to 60:40.

[0074] The method comprises the step (iii) of producing a film layer from the ink.The film layer is generally formed by depositing the ink onto a substrate to form a layer.

[0075] The coating composition may be deposited using a slot die coating process (whereby the dispersion is extruded through a slot onto the substrate by gravity or under pressure), knife coating, rod coating, inkjet printing, curtain coating, spray coating or a casting process. Preferably, the coating composition may be deposited using slot die coating, rod coating or inkjet printing. Deposition using slot die coating may be particularly preferred.

[0076] The coating composition is deposited onto a substrate to form a membrane layer. In some cases, the ion conductive membrane is formed by a single membrane layer. Alternatively, the ion conductive membrane can be formed by two or more layers (such as between two and seven layers). The number of layers will be determined by, for example, the thickness of the desired membrane and the degree of variation of the desired composition over the entire membrane (e.g., the membrane may contain one or more layers comprising a reinforcing agent polymer such as ePTFE or an additive such as a free radical reduction catalyst).

[0077] Typically, the substrate is a backing sheet, an ion conducting layer, a catalyst layer on a backing sheet, or a catalyst layer on a gas diffusion electrode. It will be appreciated by those skilled in the art that the choice of substrate will depend on the structure and production stage of the membrane.

[0078] In the case where film is formed by a single film layer or when the production of multilayer membranes begins, substrate is typically a backing layer. The backing layer provides support for the ion-conducting membrane during manufacture, and if not removed immediately, can provide support and strength during any subsequent storage and / or transmission. The material made of the backing layer should provide required support, preferably compatible with ink, preferably ink impermeable, can withstand the process conditions involved in producing the ion-conducting membrane, and can easily remove without damaging the ion-conducting membrane. The example of the material suitable for use includes fluoropolymers (such as polytetrafluoroethylene (PTFE), ethylene tetrafluoroethylene (ETFE), perfluoroalkoxy polymers (PFA), fluorinated ethylene propylene (copolymer of FEP-hexafluoropropylene and tetrafluoroethylene)) and polyolefins (such as biaxially oriented polypropylene (BOPP)).

[0079] In some cases of producing catalyst coated membranes, the catalyst layer is provided on a backing layer, for example by printing or using known coating techniques. Subsequently, the coating composition can be deposited onto the catalyst layer so that the catalyst layer is disposed between the backing layer and the membrane layer formed by depositing the ink.

[0080] In some cases, usually when the thickness of the ion conductive film is such that multiple processes are required to construct the membrane structure, the substrate is a previously formed membrane layer. It should be understood that the ion conductive film can be formed by the sequential deposition of layers. As an example, the ion conductive film can be formed as follows. In the first process, the ink containing the ion conductive polymer can be deposited on the backing layer to form the first ion conductive polymer layer, which is then dried. In the second process, the ink is deposited on the first ion conductive polymer layer to form the second ion conductive polymer layer. Subsequently, the second ion conductive polymer layer is dried. Continue this order of applying and drying to produce other ion conductive polymer layers as needed, thereby forming a desired membrane structure. It should be understood by those skilled in the art that the ink containing the recombinant catalyst as described above is used in one or more coating processes in the coating process according to the needs of the final membrane structure.

[0081] The film formed by the method as described herein can be used in the production of catalyst coated membranes. In this case, the method may include forming a catalyst layer on the first and / or second side of the film to form a step of an anode and / or cathode. It will be appreciated by those skilled in the art that the specific type of catalyst for the cathode and anode is selected according to whether the film is used for a fuel cell or an electrolyzer and whether the film is a PEM or AEM as previously described. In addition, the deposition method can be changed, for example, the catalyst layer can be transferred from a decal to the film by, for example, hot pressing, or the catalyst ink can be directly printed on the film.

[0082] The present invention also provides an ion-conducting membrane, such as a PEM or AEM, comprising a membrane layer containing a recombinant catalyst, the membrane layer comprising dispersed recombinant catalyst nanoparticles. Such a membrane is particularly suitable for electrolyzer applications. The ion-conducting membrane can be obtained by or can be obtained by the method described above.

[0083] Typically, the ion-conducting membrane has a thickness of less than or equal to 100 μm. Preferably, the membrane has a thickness of less than or equal to 95 μm, 90 μm or 85 μm. Preferably, the membrane has a thickness of at least 10 μm, such as at least 15 μm, at least 20 μm, at least 25 μm, at least 30 μm or at least 40 μm. It may be further preferred that the film has a thickness in the range of 10μm to 100μm and including 10μm and 100μm, such as in the range of 15μm to 100μm and including 15μm and 100μm, in the range of 20μm to 100μm and including 20μm and 100μm, in the range of 30μm to 100μm and including 30μm and 100μm, in the range of 30μm to 90μm and including 30μm and 90μm or in the range of 40μm to 90μm and including 40μm and 90μm.

[0084] The ion-conducting membrane thickness (and the thickness of the layers of the membrane) can be measured by scanning electron microscopy (SEM) at 0% relative humidity. The SEM analysis is performed on a cross section of the membrane and the membrane and / or layer thickness is measured at a plurality of (e.g., 10) points. Subsequently, the thickness value is determined by calculating the arithmetic mean of the measured values. Typically, SEM measurements are performed on cross sections of membranes embedded in resin, ground and polished.

[0085] The ion-conducting membrane comprises a membrane layer comprising a recombinant catalyst. It will be appreciated by those skilled in the art that the membrane may comprise more than one membrane layer comprising a recombinant catalyst, such as two or more membrane layers comprising a recombinant catalyst. It may be preferred that the membrane has a single membrane layer comprising a recombinant catalyst.

[0086] The recombinant catalyst nanoparticles are dispersed in the membrane layer. The membrane layer also comprises an ion conductive polymer and a nanoparticle stabilizer, each of which is suitably as described above with respect to the method. In this article, being dispersed in the membrane layer means that the nanoparticles are distributed throughout the membrane layer, that is, they are not located in discrete regions of this layer, such as on the surface of the reinforcing agent component. It will be appreciated by those skilled in the art that the term "dispersed" does not exclude the aggregation of nanoparticles, but in this case, the clusters themselves are distributed throughout the membrane layer.

[0087] Suitably, the recombinant catalyst nanoparticles have an average size less than 50nm, such as in the range of 1nm to 50nm and including 1nm and 50nm. Preferably, the recombinant catalyst nanoparticles have an average size in the range of 1nm to 40nm and including 1nm and 40nm, in the range of 1nm to 30nm and including 1nm and 30nm, in the range of 1nm to 20nm and including 1nm and 20nm or in the range of 1nm to 10nm and including 1nm and 10nm. The average particle size of the recombinant catalyst nanoparticles in the film can be determined by transmission electron microscopy (TEM), for example, by analyzing the cross section of the film by TEM, and measuring the size of a particle group (e.g., 100) by image analysis according to the resulting image, and then calculating the average (mean) value.

[0088] The nanoparticles of recombinant catalyst are generally in the form of discrete nanoparticle clusters. In this case, nanoparticles exist in the form of single nanoparticles, and these single nanoparticles are co-located with clusters, rather than exist in the form of nanoparticle aggregates or agglomerates, and wherein nanoparticles are bonded together by nanoparticle surface-nanoparticle surface interactions. Not subject to theoretical constraints, it is proposed that this arrangement of nanoparticles can provide the benefit relevant to the greater accessibility of hydrogen to arrive at catalytic sites. Generally, clusters have an average size in the range of 100nm to 500nm and include 100nm and 500nm. The average particle size of the recombinant catalyst nanoparticle clusters in the film can be measured by transmission electron microscopy (TEM), for example, by the cross section of TEM analytical film, and by image analysis according to the image of the resulting size of clusters (for example 100), and then calculate average (mean) value.

[0089] The membrane layer comprises a nanoparticle stabilizer as described above, such as a polymeric nanoparticle stabilizer, for example polyvinylpyrrolidone. Typically, the recombinant catalyst nanoparticles are at least partially coated with a nanoparticle stabilizer.

[0090] As described above, it may be preferred that the nanoparticle stabilizer has a higher hydrophobicity and / or a lower water absorption value than the ion-conducting polymer used in the membrane layer containing the recombination catalyst. Without being bound by theory, the use of a nanoparticle stabilizer having a higher hydrophobicity and / or a lower water absorption value than the ion-conducting polymer has the potential to improve the efficiency of the recombination catalyst by increasing the rate at which hydrogen approaches the surface of the recombination catalyst nanoparticles and promoting the removal of formed water from the catalyst surface. This provides an increased recombination rate of hydrogen and oxygen, and thus enhances protection against hydrogen permeation for a given catalyst loading in the membrane. The water absorption value of the ion-conducting polymer and the nanoparticle stabilizer can be determined by drying a sample of the material and then measuring the weight of the sample before and after immersion in water (e.g., 24 hours at 23°C). For example, water absorption value can be measured by: (i) drying the sample in an oven until the weight stabilizes; (ii) cooling the sample in a desiccator; (iii) weighing the sample; (iv) immersing the sample in water (e.g., at 23°C for 24 hours); (iv) removing the sample and patting it dry with a lint-free cloth; and (v) reweighing the sample.

[0091] Preferably, the ion-conducting membrane has a -2 Up to 30 μg / cm -2 In the range of and including 1μg / cm -2 and 30 μg / cm -2 The loading of the recombinant catalyst (e.g., platinum) is such as 5 μg / cm -2 Up to 25 μg / cm -2 In the range of and including 5μg / cm -2 and 25 μg / cm -2 , or at 8 μg / cm -2 Up to 15 μg / cm -2 The range includes 8 μg / cm -2 and 15mg / cm -2 , or at 1 μg / cm -2 Up to 10 μg / cm -2 The range includes 1 μg / cm -2 and 10 μg / cm -2 , or at 1 μg / cm -2 Up to 5 μg / cm -2 The range includes 1 μg / cm -2 and 5 μg / cm -2 This range of catalyst loadings has been found to provide an appropriate balance between reducing the level of hydrogen permeation during use and the costs associated with including the catalyst in the membrane. The catalyst loading may be determined by inductively coupled plasma mass spectrometry (ICP-MS).

[0092] Typically, the membrane layer containing the recombinant catalyst has a thickness in the range of 5 μm to 30 μm and including 5 μm and 30 μm. Compared with using a thinner catalyst layer (such as a catalyst layer applied to the membrane surface), the dispersion of nanoparticles in a membrane layer of at least 5 mm provides an improved membrane stability benefit. The use of a membrane layer containing a recombinant catalyst having a thickness greater than 30 mm does not need to significantly reduce hydrogen permeation, and may provide manufacturing difficulties, particularly when forming a non-laminated membrane structure. The thickness of the membrane layer can be determined by SEM analysis of a cross section of the membrane as described above. It may be preferred that the membrane layer containing the recombinant catalyst has a thickness in the range of 5 μm to 20 μm and including 5 μm and 20 μm, such as between 7 μm and 15 μm. Such thickness provides a suitable balance between the reduction of hydrogen permeation caused by the formed membrane and manufacturing efficiency.

[0093] Preferably, the membrane is formed by a method that does not require a lamination step to form the membrane, for example by depositing multiple layers of ion-conducting polymers on top of each other via a liquid deposition process such as printing, spraying or coating.

[0094] Preferably, the membrane is a single adhered polymer membrane comprising a plurality of ion-conducting polymer layers. As used herein, the term "adhered" means that the membrane does not contain internal lamination interfaces.

[0095] The lamination of ion-conducting membranes includes squeezing and / or bonding together at least two solid ion-conducting membranes, such membranes are optionally coated with a catalyst layer. A lamination interface is formed between the two membranes, wherein the solid surfaces of the individual membranes are pressed and / or bonded together. The lamination interface includes physical defects. In addition, the structure and / or chemical properties of the lamination interface are also different from those of the main polymer material. This is because when the solid membrane is formed, the outer surface of the solid membrane has surface features different from those in the main material. For example, a hydrophobic surface layer is formed on the membrane surface at the air interface. Raman spectroscopy can detect this difference. Therefore, when two solid membranes are pressed together, the lamination interface formed by the two solid surfaces is different in chemical and / or structural form compared to the main body of the ion-conducting polymer material. Therefore, microscopy and spectroscopy techniques can distinguish between the lamination interface between the ion-conducting polymer layers and the interface formed by a liquid deposition process (such as printing, spraying or coating of layers) to build a multilayer structure. That is, the non-laminated interface is different from the lamination interface in structure and / or chemistry, and is not just a feature of the manufacturing method. In addition, in the absence of a priori knowledge of the manufacturing method, the non-laminated interface can be identified as non-laminated in the film. Examples of analytical techniques for detecting laminated interfaces include cross-sectional SEM. Changes in crystallinity at the interface can be detected using cross-sectional TEM. Other techniques for detecting laminated interfaces include 13C / 1H / 19F solid-state NMR, neutron diffraction and / or a combination of two or more of the above techniques.

[0096] Due to physical defects and / or chemical changes at the lamination interfaces between ion-conducting polymer membranes, such interfaces can increase the resistance of the multilayer ion-conducting membrane. Therefore, it has been found to be advantageous to build the multilayer membrane structure by depositing ion-conducting polymer layers dispersed in a liquid solvent, rather than manufacturing the multilayer ion-conducting membrane via lamination of separate solid layers / films of ion-conducting polymers.

[0097] Preferably, the membrane comprises a reinforcing agent polymer, such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI). It may be preferred that the membrane layer containing the reconstitution does not comprise a reinforcing agent polymer.

[0098] The reinforcing agent material may include a porous reinforcing agent polymer sheet impregnated with an ion-conducting polymer, which reinforcing agent material is optionally expanded polytetrafluoroethylene (ePTFE). Since typical reinforcing agent polymer materials do not conduct ions, or do not conduct ions sufficiently, a porous reinforcing agent polymer is used to form the reinforcing agent layer, which is impregnated with an ion-conducting polymer through the pores of the material to provide an ion-conducting path from one side of the layer to the other side of the layer.

[0099] Preferably, the membrane comprises a radical reducing additive (e.g., a peroxide radical reducing additive, such as ceria). It should be noted that peroxides can decompose to form a series of free radicals (O, OH, OOH), and the radical reducing additive can reduce the amount of one, multiple, or all of these free radicals. The radical reducing additive can be dispersed in the membrane layer containing the recombinant.

[0100] Typically, the membrane is configured so that, with reference Figure 1 , the membrane layer (1) containing the recombination catalyst is arranged between the first ion-conducting polymer layer (2) and the second ion-conducting polymer layer (3). In such a configuration, the second face (4) of the first ion-conducting polymer layer (2) and the second face (5) of the second ion-conducting polymer layer (3) each face inwardly toward the membrane layer (1) containing the recombination catalyst. The first face (6) of the first ion-conducting polymer layer (2) and the first face (7) of the second ion-conducting polymer layer (3) are the outer surfaces of the membrane, i.e., facing the anode and cathode when incorporated into, for example, a water electrolyzer.

[0101] Suitably, the membrane consists of a membrane layer containing a recombination catalyst disposed between a first ion-conducting polymer layer and a second ion-conducting polymer layer. It will be appreciated by those skilled in the art that the first ion-conducting polymer layer and the second ion-conducting polymer layer may be formed from one or more sub-layers, which may have the same or different compositions.

[0102] In the case where the membrane is used in a PEM electrochemical device, the ion-conducting polymer present in the first ion-conducting polymer layer and the second ion-conducting polymer layer is suitably a proton-conducting polymer, and in particular a partially fluorinated sulfonic acid polymer or a fully fluorinated sulfonic acid polymer. Examples of suitable proton-conducting polymers include perfluorosulfonic acid ionomers. It is preferred that the ion-conducting polymer in the first ion-conducting layer and / or the second ion-conducting layer is the same as the ion-conducting polymer in the membrane layer containing the recombinant catalyst. It is alternatively preferred that the ion-conducting polymer in the first ion-conducting layer and / or the second ion-conducting layer is different from the ion-conducting polymer in the membrane layer containing the recombinant catalyst.

[0103] Typically, a strengthener polymer and / or a free radical reducing agent (eg, a peroxide free radical reducing additive such as ceria) is present in the first ion conducting polymer layer and / or the second ion conducting polymer layer.

[0104] Preferably, the thickness of the first ion-conducting polymer layer is less than the thickness of the second ion-conducting polymer layer. This asymmetry enables the membrane layer containing the recombination catalyst to be placed closer to the anode than the cathode in a water electrolyzer configuration, which is believed to be beneficial in reducing hydrogen permeation.

[0105] It may be preferred that the first ion conductive polymer layer has a thickness in the range of 5 μm to 30 μm and including 5 μm and 30 μm, such as in the range of 5 μm to 20 μm and including 5 μm and 20 μm, or in the range of 5 μm to 15 μm and including 5 μm and 15 μm, or in the range of 7 μm to 15 μm and including 7 μm and 15 μm. Such thickness of the first ion conductive polymer layer is considered by the inventors to provide a suitable distance between the anode layer and the recombination catalyst in the formed CCM for water electrolyzer to provide a significant reduction in hydrogen permeation.

[0106] Preferably, the second ion conductive polymer layer has a thickness in the range of 10 μm to 90 μm and including 10 μm and 90 μm, such as in the range of 20 μm to 70 μm and including 20 μm and 70 μm, in the range of 40 μm to 70 μm and including 40 μm and 70 μm, or in the range of 25 μm to 45 μm and including 25 μm and 45 μm.

[0107] The thickness of the ion-conducting polymer layer can be adjusted, for example, by varying the number of multiple deposition steps of the ion-conducting polymer during the membrane manufacturing process, or by varying the pump speed during the deposition of the ion-conducting polymer.

[0108] Preferably, the membrane comprises or consists of: (i) a first ion-conducting layer having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm; (ii) a second ion-conducting layer having a thickness in the range of 25 μm to 45 μm and including 25 μm and 45 μm; and (iii) a membrane layer containing a recombinant catalyst having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm and being disposed between the first ion-conducting layer and the second ion-conducting layer. In such a configuration, preferably, the second ion-conducting layer comprises a strengthener polymer, such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI). It has been found that such a membrane structure provides a particularly suitable balance between membrane resistance and hydrogen permeation level.

[0109] It is preferred that the membrane comprises or consists of: (i) a first ion-conducting layer having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm; (ii) a second ion-conducting layer having a thickness in the range of 40 μm to 70 μm and including 40 μm and 70 μm; and (iii) a membrane layer containing a recombinant catalyst having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm and being disposed between the first ion-conducting layer and the second ion-conducting layer. In such a configuration, it is preferred that the second ion-conducting layer comprises a strengthener polymer, such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI). It is further preferred that the second ion-conducting layer contains two strengthener polymer regions, such as two sublayers comprising a strengthener polymer, such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI). Such membrane structures enable operation at particularly high gas pressure differentials across the membrane while maintaining hydrogen permeation and low membrane resistance.

[0110] Membranes as described herein may be suitably used as part of a catalyst coated membrane (CCM). Such CCMs have an anode catalyst layer and / or a cathode catalyst layer applied to the face of the membrane. These membranes may also be used in systems where one or more of the anode catalyst layer and the cathode catalyst layer are applied to a substrate located on either side of the membrane (such as a gas diffusion layer or a porous transport layer).

[0111] In the case of a CCM for a water electrolyzer, a cathode catalyst layer may be applied to the surface of a membrane comprising a catalyst for catalyzing the hydrogen evolution reaction. Preferably, the cathode catalyst layer comprises platinum, such as a carbon-supported platinum catalyst. The catalyst material may be formulated as an ink, printed onto a PTFE sheet ex situ, and transferred to the membrane by hot pressing. Alternatively, the ink may be applied directly to the membrane.

[0112] In the case of a CCM for a water electrolyser, an anode catalyst layer may be applied to the surface of the membrane comprising a catalyst for catalyzing the oxygen evolution reaction. In the case of a CCM for a PEMWE, it may be preferred that the anode catalyst layer comprises iridium, such as iridium oxide or a mixed oxide of iridium and another metal or metals.

[0113] The anode material may be formulated as an ink, suitably in an ionically conductive polymer, printed ex situ onto a PTFE sheet, and transferred to the membrane by heat pressing. Alternatively, the ink may be coated directly onto the membrane.

[0114] Typically, the CCM comprises a membrane comprising a first ion-conducting polymer layer and a second ion-conducting polymer layer, wherein the membrane layer containing the recombination catalyst is disposed between the first ion-conducting polymer layer and the second ion-conducting polymer layer, as described above. Preferably, the CCM is configured such that the membrane layer containing the recombination catalyst is closer to the anode catalyst layer than the cathode catalyst layer. It may be further preferred that the thickness of the second ion-conducting polymer layer is greater than the thickness of the first ion-conducting polymer layer. Such configurations are proposed to have benefits in reducing hydrogen permeation.

[0115] Suitably, the CCM is configured such that, with reference to Figure 2 The second side (4) of the first ion-conducting polymer layer (2) and the second side (5) of the second ion-conducting polymer layer (3) each face inward toward the membrane layer (1) containing the recombination catalyst. The anode catalyst layer (8) (if present) is disposed on the first side (6) of the first ion-conducting polymer layer (2). The cathode catalyst layer (9) (if present) is disposed on the first side (6) of the second ion-conducting polymer layer (3).

[0116] Preferably, the catalyst coated membrane comprises a membrane comprising or consisting of: (i) a first ion conductive layer having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm; (ii) a second ion conductive layer having a thickness in the range of 25 μm to 45 μm and including 25 μm and 45 μm; and (iii) a membrane layer containing a recombinant catalyst having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm and being arranged between the first ion conductive layer and the second ion conductive layer, and wherein the second face of the first ion conductive polymer layer and the second face of the second ion conductive polymer layer each face inwardly toward the membrane layer containing the recombinant catalyst, and wherein the anode catalyst layer as described above is arranged on the first face of the first ion conductive layer and / or the cathode catalyst layer as described above is arranged on the first face of the second ion conductive layer. In such configurations, it is preferred that the second ion-conducting layer comprises a strengthener polymer, such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI).

[0117] Preferably, the catalyst coated membrane comprises a membrane comprising or consisting of: (i) a first ion conductive layer having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm; (ii) a second ion conductive layer having a thickness in the range of 40 μm to 70 μm and including 40 μm and 70 μm; and (iii) a membrane layer containing a recombinant catalyst having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm and being arranged between the first ion conductive layer and the second ion conductive layer, and wherein the second face of the first ion conductive polymer layer and the second face of the second ion conductive polymer layer each face inwardly toward the membrane layer containing the recombinant catalyst, and wherein the anode catalyst layer as described above is arranged on the first face of the first ion conductive layer and / or the cathode catalyst layer as described above is arranged on the first face of the second ion conductive layer. In such configurations, it is preferred that the second ion-conducting layer comprises a strengthener polymer, such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI). It may be further preferred that the second ion-conducting layer contains two strengthener polymer regions, such as two sublayers comprising a strengthener polymer, such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI).

[0118] The present invention will now be described with reference to the following examples, which are provided to aid understanding of the present invention and are not intended to limit the scope of the present invention.

[0119] Example

[0120] Example 1 - Formation of a Stabilized Dispersion of Platinum Nanoparticles Using PVP .

[0121] A PVP-stabilized dispersion of platinum nanoparticles in water was prepared from an aqueous solution of platinum nitrate and a 2 w / v% aqueous solution of PVP (MW 10,000) using a continuous flow hydrothermal reactor operated at elevated temperature and pressure. The Pt loading in the dispersion was 3.93 g / L measured using ICP.

[0122] Dynamic light scattering (DLS) analysis showed that the z-average size of the PVP-Pt clusters in the dispersion was 280 nm, whereas small angle X-ray scattering (SAXS) analysis showed that the size of the platinum nanoparticles ranged from 1 nm to 10 nm.

[0123] Example 2 - Formation of an ink containing PVP-stabilized platinum nanoparticles and an ionically conductive polymer

[0124] The aqueous dispersion prepared in Example 1 was mixed with additional water and EtOH to produce an ethanol-water mixture (wt% ratio 4:1). Dry PFSA ionomer (3M Corporation, EW-800) was added to produce a ˜17 wt% ionomer and 0.08 wt% Pt ink. The ink was mixed using a roll mixer.

[0125] Dynamic light scattering (DLS) analysis showed that the z-average diameter of the Pt-PVP clusters in the dispersion was 1200 nm.

[0126] The stability of the ink during storage was evaluated by measuring the z-average diameter after 1 day and after 3 months. The results are shown in Figure 3 , which showed no change in the DLS analysis curve, indicating high stability and resistance to agglomeration.

[0127] Example 3 - Preparation of a membrane including a platinum-containing membrane layer

[0128] A membrane containing a platinum-containing membrane layer was prepared by knife coating an ink layer prepared according to the method of Example 2 onto a 15 μm thick PFSA membrane and drying the formed layer at room temperature.

[0129] The cross section of the formed film was analyzed by scanning electron microscopy with energy dispersive X-ray analysis (SEM-EDX). This showed that the platinum-containing film layer had a thickness of about 30 μm. An enlarged cross section of the SEM-EDX image of the platinum-containing film layer is shown in Figure 4 This indicates that the platinum nanoparticles are distributed throughout the film layer.

[0130] Example 4 - Preparation of a film comprising a platinum-containing film layer and analysis by cryo-TEM

[0131] The ink prepared according to Example 2 was frozen in a cryostat using liquid nitrogen and cut into sections using a diamond knife. One section was placed on a copper grid and thawed to form a film <100 nm thick.

[0132] The formed film was analyzed by cryogenic transmission electron microscopy (cryoTEM).This analysis showed that the platinum nanoparticles in the film had an average particle size in the range of 1 nm to 10 nm and were in the form of discrete Pt nanoparticle clusters.

[0133] The average nearest neighbor distance between platinum particles was measured from cryoTEM images using an algorithm. This data was compared to analysis of a comparative film incorporating a platinum-containing film layer having the same Pt ​​loading but prepared from an ink containing Pt particles from a platinum black source without any stabilizer. This shows that when a film is formed from a stabilized nanoparticle dispersion, the interparticle distance is significantly reduced, thereby increasing the dispersion of Pt in the film layer.

[0134] Example 5 - Formation of a CCM Incorporating a Membrane Having a Platinum-Containing Membrane Layer and Hydrogen Permeation Testing .

[0135] Composite membranes with a thickness of ∼105 mm were prepared by casting a 10 mm thick recombinant catalyst layer (using the method described in Example 3) on an 80 μm PFSA membrane and then laminating the product on a 15 μm thick PFSA membrane such that the recombinant catalyst layer was located between the two PFSA membranes. -2 Pt) and IrOx anode catalyst layer (with Ir loading of 2 mg cm -2 ) was laminated on either side of the composite film to obtain a CCM. Lamination was achieved by hot pressing at 173°C and 800PSI for 2 minutes.

[0136] Comparative examples of CCMs were also prepared with the same catalyst layers formed on: (i) an 80 micron PFSA membrane without any recombinant catalyst ( Figure 5 and (ii) a membrane prepared as in Example 5, but with the recombinant catalyst layer formed from an ink to which Pt particles were added (without using a stabilized dispersion of nanoparticles, Figure 5 in the table).

[0137] Testing of Catalyst Coated Membranes (CCM)

[0138] Hydrogen permeation

[0139] The hydrogen permeation level of each CCM was measured at different pressures using the following method:

[0140] A water electrolysis cell incorporating the catalyst coated membrane to be tested was prepared. The cell temperature was maintained at 80°C, and the anode pressure and cathode pressure were set to 2 bar. Next, the current density was set to 2 A / cm 2The cathode pressure was increased stepwise from 2 bar to 6 bar to 10 bar, with each step lasting a minimum of 45 minutes. The H2% in oxygen at the anode gas outlet was measured by a compact GC 4.0 gas chromatograph (GC) from Global Analysis Solutions. The CCM with PVP-Pt particles in the membrane did not reach equilibrium at the 2 bar test before the pressure change, so no data is given for this value, however it remained below 0.4% hydrogen permeation.

[0141] Figure 5 The results of hydrogen permeation testing of CCMs are shown. These results show that the membrane formed from PVP-Pt particles provides the greatest reduction in hydrogen permeation.

[0142] Example 6 - Formation of a Stabilized Dispersion of Platinum Nanoparticles Using PVP and Formaldehyde .

[0143] Pt(NO3)4 (equivalent to 1 g Pt) was added to water (500 mL) and stirred. PVP10 (average molecular weight 10,000, 8.5 g) was added, followed by formaldehyde (37% in water, 20.8 g). The mixture was heated to 68°C, then cooled to room temperature and stirred overnight to form a dispersion.

[0144] Example 7 - Formation of Ion Conducting Polymer Inks Containing PVP Stabilized Nanoparticles

[0145] The stabilized Pt nanoparticle aqueous dispersion (formed according to a method similar to Example 6) was mixed with ethanol and water to produce a mixture with an ethanol: water weight ratio of 80:20. Dry ionomer (3M Company, 800EW) was added to the mixture to produce a dispersion in which the ionomer solids were ~17% wt.

[0146] Example 8 - Hydrogen Permeation Testing at a Range of Pt Loadings

[0147] A series of catalyst coated membranes were prepared with different loadings of stabilized Pt nanoparticles and the following structures:

[0148] (1) Positive electrode layer containing Pt / C

[0149] (2) ~60 micron PFSA membrane (with two ePTFE reinforcements)

[0150] (3) ~10 μm Pt-containing recombination catalyst layer

[0151] (4) ~10 micron PFSA membrane layer

[0152] (5) Negative electrode layer containing iridium oxide (IrOx)

[0153] Layers 2, 3 and 4 were applied using a film applicator (slot die and lacquer baker).Layers 1 and 5 were attached to the composite layer 2-3-4 using lamination at a temperature above the ionomer transition temperature (160°C).

[0154] The recombinant catalyst layer was prepared with: (i) a catalyst layer containing PVP stabilized Pt nanoparticles ( Figure 6 or (ii) an ionically conductive polymer ink containing unsupported Pt particles (without PVP) ( Figure 6 Ion-conducting polymer ink containing “Pt particles” in the matrix.

[0155] Testing the hydrogen permeation of CCM, such as Figure 6 This demonstrates that the use of a stabilized nanoparticle dispersion (Pt-PVP) allows for nearly complete reaction of hydrogen across the membrane under the conditions tested even at low platinum loadings, with significantly improved performance when considered alongside a comparative CCM prepared without a stabilized nanoparticle dispersion.

Claims

1. A method for producing an ion-conducting membrane comprising a membrane layer containing a recombination catalyst, the method comprising the following steps: (i) providing a stabilized dispersion of recombinant catalyst nanoparticles; (ii) mixing the stabilized dispersion with an ion-conducting polymer to form an ink; (iii) producing the film layer from the ink.

2. The method of claim 1, wherein the recombinant catalyst nanoparticles comprise platinum and / or palladium.

3. A method according to claim 1 or claim 2, wherein the stabilized dispersion of recombinant catalyst nanoparticles comprises a nanoparticle stabilizer having a higher hydrophobicity and / or a lower water absorption value than the ion-conducting polymer used in step (ii).

4. The method according to any one of the preceding claims, wherein the stabilized dispersion comprises a polymeric nanoparticle stabilizer.

5. The method of claim 3 or claim 4, wherein the nanoparticle stabilizer is polyvinylpyrrolidone (PVP).

6. A method according to any one of the preceding claims, wherein step (iii) comprises depositing the ink onto a substrate such as a backing sheet, an ion-conducting polymer layer or a catalyst layer on a backing sheet.

7. A method according to claim 6, wherein the substrate is a first ion-conducting polymer layer, and the method comprises step (iv) adding a second ion-conducting polymer layer so that the membrane layer containing the recombination catalyst is arranged between the first ion-conducting polymer layer and the second ion-conducting polymer layer.

8. A method according to any one of the preceding claims, further comprising the step of forming a catalyst layer on at least one face of the membrane to form a catalyst coated membrane.

9. The method of claim 8, further comprising the step of applying a sealing material to at least one face of the catalyst coated membrane.

10. An ink for making an ion-conducting membrane, the ink comprising recombinant catalyst nanoparticles, a nanoparticle stabilizer, and an ion-conducting polymer.

11. The ink of claim 10, wherein the nanoparticle stabilizer is polyvinyl pyrrolidone.

12. An ion-conducting membrane for use in an electrochemical device such as a fuel cell or a water electrolyser, wherein the ion-conducting membrane is produced by a method according to any one of claims 1 to 9 or using an ink according to claim 10 or claim 11.

13. An ion-conducting membrane for an electrochemical device such as a fuel cell or a water electrolyzer, the ion-conducting membrane comprising a membrane layer containing a recombinant catalyst, the membrane layer comprising dispersed recombinant catalyst nanoparticles, a nanoparticle stabilizer, and an ion-conducting polymer.

14. An ion-conducting membrane according to claim 13, wherein the nanoparticle stabiliser has a higher hydrophobicity and / or a lower water absorption value than the ion-conducting polymer.

15. An ion-conducting membrane according to claim 13 or claim 14, wherein the recombinant catalyst nanoparticles are in the form of discrete nanoparticle clusters.

16. An ion-conducting membrane according to any one of claims 13 to 15, wherein the nanoparticle stabiliser is a polymer such as polyvinylpyrrolidone.

17. An ion-conducting membrane according to any one of claims 13 to 16, wherein the recombinant catalyst nanoparticles are at least partially coated with the nanoparticle stabiliser.

18. An ion-conducting membrane according to any one of claims 13 to 17, wherein the nanoparticles have an average particle size of less than 50 nm.

19. An ion-conducting membrane according to any one of claims 13 to 18, wherein the membrane has a thickness in the range of 30 μm to 90 μm, inclusive.

20. An ion-conducting membrane according to any one of claims 13 to 19, wherein the recombination catalyst-containing membrane layer has a thickness in the range of 5 μm to 30 μm, inclusive.

21. An ion-conducting membrane according to any one of claims 13 to 20, wherein the membrane is a single coherent polymer membrane comprising a plurality of ion-conducting polymer layers.

22. An ion-conducting membrane according to any one of claims 13 to 21, comprising a first ion-conducting polymer layer and a second ion-conducting polymer layer, and wherein the membrane layer containing the recombination catalyst is arranged between the first ion-conducting polymer layer and the second ion-conducting polymer layer.

23. An ion-conducting membrane according to claim 22, wherein the first ion-conducting polymer layer has a thickness in the range of 5 μm to 30 μm, inclusive, preferably in the range of 5 μm to 20 μm, inclusive.

24. An ion conducting membrane according to claim 22 or claim 23, wherein the second ion conducting polymer layer has a thickness in the range 10 to 90 μm, preferably in the range 40 to 70 μm and inclusive.

25. A catalyst coated membrane for use in an electrochemical device such as a fuel cell or a water electrolyser, the catalyst coated membrane comprising an ion conducting membrane according to any one of claims 12 to 24.

26. A water electrolyser comprising the ion-conducting membrane of any one of claims 12 to 24 or the catalyst-coated membrane of claim 25.

27. A fuel cell comprising the ion-conducting membrane according to any one of claims 12 to 24 or the catalyst-coated membrane according to claim 25.

Citation Information

Patent Citations

  • Reinforced membrane, electrochemical cell and fuel cell comprising same, and production method for reinforced membrane

    US10476094B2

  • COLLOIDAL DISPERSIONS COMPRISING PRECIOUS METAL PARTICLES AND ACIDIC lONOMER COMPONENTS AND METHODS OF THEIR MANUFACTURE AND USE

    US20150236354A1

  • Mixing reactor and method

    WO2015075439A1

  • membrane

    WO2020148545A1